2020
DOI: 10.1002/batt.202000210
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen in Lithium−Oxygen Batteries

Abstract: Singlet oxygen (1O2) is one of the most critical species leading to parasitic side reactions and poor reversibility in non‐aqueous Li−O2 batteries. 1O2 is generated via the disproportionation of the superoxide radical (O2.−) in O2/Li2O2 electrochemistry. The mechanistic and computational studies on 1O2 formation revealed the significant roles of the associated cations, solvation ability of aprotic solvents, H+ source, and catalyst/electrode materials. Along with efforts to alleviate 1O2 production, trapping an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…In particular, LiO 2 is a radical intermediate both in the electrochemical reduction of O 2 and in the oxidation of Li 2 O 2 . , Despite its simplicity, reactions such as hide a very complex mechanism that involves singlet–triplet spin intersystem crossing while evolving from two doublet LiO 2 radicals. Due to the coexistence of electronic states of different multiplicities, the disproportionation product can be either 1 O 2 (singlet oxygen) or 3 O 2 (triplet, ground-state oxygen). , The formation of singlet oxygen, which is a highly reactive biradical molecule, is at the origin of parasitic degradation reactions during electrochemical charge/discharge cycles. As expected, 1 O 2 release leads to battery death upon cycling. …”
Section: Introductionsupporting
confidence: 69%
“…In particular, LiO 2 is a radical intermediate both in the electrochemical reduction of O 2 and in the oxidation of Li 2 O 2 . , Despite its simplicity, reactions such as hide a very complex mechanism that involves singlet–triplet spin intersystem crossing while evolving from two doublet LiO 2 radicals. Due to the coexistence of electronic states of different multiplicities, the disproportionation product can be either 1 O 2 (singlet oxygen) or 3 O 2 (triplet, ground-state oxygen). , The formation of singlet oxygen, which is a highly reactive biradical molecule, is at the origin of parasitic degradation reactions during electrochemical charge/discharge cycles. As expected, 1 O 2 release leads to battery death upon cycling. …”
Section: Introductionsupporting
confidence: 69%
“…As with the C 1s spectra of the deeply charged cathodes (Figure b,f), a generally intensified oxidation can be observed in all four regions, including the increase of the above-mentioned C–O bond from the degraded TEGDME solvent as well as the CO bond from further oxidation of the C–O bond. The disappearance of the HCOO– peak in Region D suggested that it can be decomposed, while its appearance in Regions A and B after charge may be related to the local side reactions of the solvent with the singlet oxygen formed by the Li 2 O 2 oxidation during charge due to their almost 3 times yield as that of Region D. Besides, the number of “C-C” from the SP carbon substrate also decreased in these regions, further implying the worsening and corrosion of the initial carbon surface after charge. Moreover, all of the −CF 2 signals of the binder in the four regions disappeared, which should have been covered by the thick byproduct layer as shown in the SEM images in Figure a′–d′, as the XPS technique only gives the surface information within about 2–10 nm in depth.…”
Section: Resultsmentioning
confidence: 93%
“…These results reveal the necessity of limiting the Li 2 CO 3 quantity in Li-O 2 /CO 2 cells. In addition, the elongated capacity over 4 V suggested the decomposition of carbonaceous electrodes and electrolyte solution and the possible formation of singlet oxygen, causing capacity fading. ,, …”
Section: Identification Of Discharge Products In Li-o2/co2 Cellsmentioning
confidence: 99%